Are formalised implementation activities associated with aspects of quality of care in general practice? A cross-sectional study. Issue 2 (2017) - Le, Jette V; Lykkegaard, Jesper; Pedersen, Line B; Riisgaard, Helle; Nexøe, Jørgen; Lemmergaard, Jeanette; Søndergaard, Jens
No abstract available